2014
DOI: 10.15390/eb.2014.3335
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Relationship between Academic Burnout and Classroom Assessment Environment

Abstract: KeywordsIn this study, we aimed to examine the relationship between academic burnout and the classroom assessment environment. A causal-comparative model was employed in this study, which was carried out with 496 high school students in the provinces of Batman and Diyarbakir in Turkey in the spring of 2013-2014. The Maslach Burnout Inventory-Student Form (MBI-SF), which was developed by Schaufeli et al. (2002) and adapted into Turkish by Capri, Gunduz and Gokcakan (2011), was employed in the study to measure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The level of academic burn-out varied according to their views of the classroom evaluation environment. There was a negative correlation between students' learning-oriented perception (the process of effort is more important) and the level of academic burn-out, while there was a positive correlation between students' performance-oriented perception (the result is more important) and the level of academic burnout [17]. Shih's study also showed that the learning environment and academic burn-out level was significantly influenced by the structured will, when students perceived higher levels of classroom structure, namely the teacher provided clear expectations and direction, with the guiding framework of learning activities, students were more likely to adopt positive coping styles, also showed lower levels of academic burnout [15].…”
Section: External Factorsmentioning
confidence: 90%
“…The level of academic burn-out varied according to their views of the classroom evaluation environment. There was a negative correlation between students' learning-oriented perception (the process of effort is more important) and the level of academic burn-out, while there was a positive correlation between students' performance-oriented perception (the result is more important) and the level of academic burnout [17]. Shih's study also showed that the learning environment and academic burn-out level was significantly influenced by the structured will, when students perceived higher levels of classroom structure, namely the teacher provided clear expectations and direction, with the guiding framework of learning activities, students were more likely to adopt positive coping styles, also showed lower levels of academic burnout [15].…”
Section: External Factorsmentioning
confidence: 90%
“…The inappropriate use of digital technology can reduce students’ perception of the school climate, and this negative state can reduce the sense of belonging and identification with the university [ 79 ]. Thus, students’ perception of the classroom environment constitutes an important variable in predicting their level of academic burnout [ 80 ].…”
Section: Literature Reviewmentioning
confidence: 99%